Intersectionality and restorative juvenile justice - Tello Gilardi, Janet (2022)
This research analyzes, based on an intersectionality approach, the results of surveys made to adolescents in conflict with criminal law, who are inmates in youth detention centers in Peru, in 2021. The findings indicate the concurrence of various conditions of vulnerability that continue to be risk factors, which have not necessarily been addressed by the juvenile penitentiary system nor point to the application of the model of restorative juvenile justice.